Settling for efficiency – A framework for the European securities transaction industry - Serifsoy, Baris; Weiß, Marco (Journal of Banking & Finance, 2007)
Despite a lot of restructuring and many innovations in recent years, the securities transaction industry in the European Union is still a highly inefficient and inconsistently configured system for cross-border transactions. This paper analyzes the functions performed, the institutions involved and the parameters concerned that shape market and ownership structure in the industry. Of particular interest are microeconomic incentives of the main players that can be in contradiction to social welfare. We develop a framework and analyze three consistent systems for the securities transaction industry in the EU that offer superior efficiency than the current, inefficient arrangement. Some policy advice is given to select the ‘best’ system for the Single European Financial Market.